Avaliação do estresse oxidativo em pacientes esquizofrênicos - Borghi, Fábio Aparecido (2016)
Introduction: Schizophrenia is a complex Neuropsychiatric disorder of uncertain etiology. About 30% of the affected population do not respond to the usual treatment with antipsychotic medication, therefore, they are considered a subgroup of refractory schizophrenics. Several different lines of research has been developed to understand the mechanisms related to the pathophysiology of Schizophrenia, standing out the role of oxidative stress. Objectives: To evaluate the oxidative stress biomarkers in Schizophrenia, and uncover a possible association to patients known to be refractory to antipsychotic treatment, also comparing positive and negative symptoms of schizophrenia on the schizophrenic population currently being treated at a tertiary healthcare center. Methods: Eightynine individuals were selected and divided into three groups: G1 - 36 healthy subjects (control group); G2 - 26 non-refractory schizophrenia patients; G3 - 27 refractory schizophrenia patients. All patients met the criteria for Schizophrenia diagnosis, as proposed by DSM-IV (Diagnostic and Statistical Manual of Mental Disorders). The Kane et al. criteria and IPAP algorithms (International Psychopharmacology Algorithm Project) were also used to determine the presence of clinically refractory Schizophrenia. Clinical and sociodemographic data of groups were collected, analyzed and compared. For the clinical assessment of the patient’s psychopathological state, the PANSS (Positive and Negative Syndrome Scale) tool was used. The patients had peripheral blood drawn for the measurements of oxidative stress biomarkers: malondialdehyde (MDA), total antioxidant capacity (TEAC), catalase (CAT) and glutathione peroxidase (GSH-Px), using the methodology of high performance liquid chromatography resolution and spectrophotometry. The Chi-Square test (χ2), Fisher’s exact test and Mann- Whitney non-paired test were used for statistical analysis. Results: There was MDA and CAT increase in the patient groups (G2 and G3) as compared to the control group (G1). The enzymatic activity of GSH-Px was reduced in G2 and G3 as compared to the control group. TEAC plasma levels remained similar among all groups. There was no statistic relevant difference among the patient groups concerning the analysis of all the studied biomarkers (MDA, TEAC, CAT and GSHPx). The scores obtained by the PANSS scale also showed no differences between the two groups of patients. The patient groups were similar on sociodemographic and lifestyle habits. Conclusion: Serum MDA, CAT and GSHPx were positively associated to Schizophrenia, unlike TEAC, which was not associated to this condition. Regarding clinical refractority, none of the studied biomarkers was associated to this schizophrenia characteristic, as well as the scores obtained by the PANSS, sociodemographic data and lifestyle habits.